Digital Public Service Delivery in Local Governments: A Literature Review on Administrative Capacity and Citizen Readiness - Apri Widyastik; Amirul Mustofa; Ulul Albab; Sri Kamariyah (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2026)
The digital transformation of public service delivery has become a central agenda in contemporary public administration, positioning local governments as critical actors in translating national digital strategies into tangible, citizen-facing outcomes. Despite rapid diffusion of digital platforms and e-government initiatives, substantial variation persists in the performance, inclusiveness, and sustainability of digital public services across local contexts. This variation points to persistent challenges related to administrative capacity constraints within local governments and uneven levels of citizen readiness to access and use digital services. Addressing these challenges, this article presents a comprehensive literature review that aims to (1) map the conceptual evolution of digital public service delivery in local governments, (2) synthesize empirical findings on the roles of administrative capacity and citizen readiness, and (3) identify key theoretical and empirical gaps in the existing scholarship. Methodologically, the study adopts a systematic literature review approach, drawing on peer-reviewed journal articles published in the last five years and indexed in major academic databases, including Scopus, Web of Science, DOAJ, and Google Scholar. The selected literature is analyzed using thematic synthesis, guided by an integrated theoretical framework combining Digital Government Theory and Digital Era Governance as overarching transformation lenses, Administrative Capacity and Capacity Building Theory and Competency-Based Human Resource Management to explain organizational and human resource determinants, Digital Divide Theory and the Technology Acceptance Model to capture citizen-side readiness and adoption dynamics, and Policy Implementation Theory to account for institutional and regulatory mediation. The synthesis reveals several dominant patterns: digital service performance is strongly conditioned by leadership, coordination, information capacity, and workforce competencies; citizen uptake is shaped not only by access and skills but also by perceived usefulness, ease of use, and trust; and policy design and implementation processes mediate the interaction between supply-side capacity and demand-side readiness. Importantly, the review shows that these factors are mutually constitutive rather than independent, challenging linear and technology-centric models of digital transformation. The article concludes by advancing an integrative conceptual understanding of local digital public service delivery and by outlining theoretical implications for digital public administration research as well as practical policy recommendations for designing inclusive, capacity-sensitive, and sustainable digital public services at the local level.